A Descriptive Analysis of the Interactions During Clinical Supervision - Novoa-Gómez, Mónica; Córdoba-Salgado, Oscar; Rojas, Natalia; Sosa, Luis; Cifuentes, David; Robayo, Sara (Frontiers in Psychology, 2019)
This study intends to analyze some skills trained during supervision. In it we describe sets of interactions (based on the American Psychological Association [APA], 2006; competency domains) happened between the supervisor and the supervisee during the supervision process. Interactions from twelve supervisor-supervisee dyads during asynchronous and direct, and individual and group supervision sessions were video recorded for this purpose. The recordings helped to determine, classify, and define behavioral response classes in each dyad’s interactions. Percentages of time spent in each behavior class were computed. A reliability of 95% CI [0.91, 0.95] among observers was obtained. The behavior classes in which more time was spent were assessment, intervention, and conceptualization skills. Behavior classes in which less time was spent were related to emotional and interpersonal processes. These findings are discussed by linking the evidence-based theory on supervision with the time spent in each behavior class.